Tanggung Jawab Hukum Pemerintah Atas Ketimpangan Fasilitas Pelayanan Kesehatan dalam Pemenuhan Hak Atas Kesehatan di Indonesia - Dafirly Salsadilla Dosanto; Riski Ananda Kusuma Putri; Alya Synthia Kurniawati; Muhammad Thufail Ariiq; Siti Fadila Nuramelia; Misshouw Meilany Putri; Muhammad Abdul Azis (Jurnal Multidisiplin Indonesia, 2026)
Inequality in health care facilities remains a legal problem because the right to health requires health services to be available, accessible, qualified, and non-discriminatory. This study analyzes the legal construction of health facility inequality in fulfilling the right to health in Indonesia and formulates a prescriptive model for strengthening the responsibility of the central and local governments. This research uses normative legal research with statutory and conceptual approaches, while the analysis is conducted descriptively and prescriptively. The study finds that health facility inequality cannot be reduced to differences in the number of facilities because it also concerns the distribution of authority, minimum service standards, availability of health workers, digital infrastructure, financing, referral systems, and supervision. Indonesian health law has regulated the government’s responsibility for equitable access, yet it has not fully established an accountability mechanism connecting equitable distribution with planning, budgeting, evaluation, and policy correction. This study proposes a rights-based accountability model for health facility equalization by integrating needs mapping, minimum standards, affirmative policy for vulnerable regions, data integration, participatory evaluation, and administrative incentives and sanctions.